Where Web Services Meet Mobile Devices the challenges to be met. - Linthicum, David S. (SOA webservices journal.)
Let's face it, we're going mobile. You only need to consider how you communicate these days to understand that, I, for one, find that my Blackberry is becoming my e-mail terminal of choice. as well as my best source of information via the WAP-enabled Web browser built-in. And onh yes, it's a phone. Others are finding that their mobile phones are their single point of contact, both voice and data, and this trend will only continue as we learn to cut the wires and as wireless networks become more pervasive and much faster.